2012
DOI: 10.1186/2229-0443-2-2-73
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of Computerized TOEFL Test

Abstract: The present study investigated students' perception of computerized TOEFL test. Subject of this study were 100 adult male and female students who took the iBT TOEFL test in Iran. Participants were provided with a researcher-developed questionnaire on the advantages and disadvantages of Computer-Based Test (CBT) compared to PaperBased Test (PBT). The collected data were analyzed using descriptive statistics and factor analysis to investigate the perceptions of the students. Results of this study showed that stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
3
1
Order By: Relevance
“…The results of a study that found Iranian students’ perception on using computers mostly disadvantageous [ 34 ] came in contrast with the present study which found an overall positive student attitude towards CBT. It can partly relate to the nature of the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of a study that found Iranian students’ perception on using computers mostly disadvantageous [ 34 ] came in contrast with the present study which found an overall positive student attitude towards CBT. It can partly relate to the nature of the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, some students felt distracted by the noise of computer keyboards, as they had to switch between the two screens and the video, and this affected their concentration (Fluck et al., 2009). Besides that, students with poor typing ability saw the use of e-exams as a disadvantage (Noubandegani, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies regarding the test takers' perception. Some of them focused on the value of test preparation [14,15], the comparison between IELTS & TOEFL Suryaningsih the test deliverycomputerized vs. noncomputerized Noubandegani and relation between TOEFL and academic performance [12,16,17]. Nonetheless, studies on test takers' perception regarding the use of TOEFL as an exit requirement are relatively rare.…”
Section: Introductionmentioning
confidence: 99%